PGL I expression in live bacteria allows activation of a CD206/PPARγ cross-talk that may contribute to successful Mycobacterium leprae colonization of peripheral nerves. - Chyntia Carolina Díaz Acosta; André Alves Dias; Thabatta Leal Silveira Andrezo Rosa; Leonardo Ribeiro Batista-Silva; Patricia Sammarco Rosa; Thiago Gomes Toledo-Pinto; Fabrício da Mota Ramalho Costa; Flávio Alves Lara; Luciana Silva Rodrigues; Katherine Antunes Mattos; Euzenir Nunes Sarno; Patrícia Torres Bozza; et al. (PLoS Pathogens)
Mycobacterium leprae, an obligate intracellular bacillus, infects Schwann cells (SCs), leading to peripheral nerve damage, the most severe leprosy symptom. In the present study, we revisited the involvement of phenolic glycolipid I (PGL I), an abundant, private, surface M. leprae molecule, in M. leprae-SC interaction by using a recombinant strain of M. bovis BCG engineered to express this glycolipid. We demonstrate that PGL I is essential for bacterial adhesion and SC internalization. We also show that live mycobacterium-producing PGL I induces the expression of the endocytic mannose receptor (MR/CD206) in infected cells in a peroxisome proliferator-activated receptor gamma (PPARγ)-dependent manner. Of note, blocking mannose recognition decreased bacterial entry and survival, pointing to a role for this alternative recognition pathway in bacterial pathogenesis in the nerve. Moreover, an active crosstalk between CD206 and the nuclear receptor PPARγ was detected that led to the induction of lipid droplets (LDs) formation and prostaglandin E2 (PGE2), previously described as fundamental players in bacterial pathogenesis. Finally, this pathway was shown to induce IL-8 secretion. Altogether, our study provides evidence that the entry of live M. leprae through PGL I recognition modulates the SC phenotype, favoring intracellular bacterial persistence with the concomitant secretion of inflammatory mediators that may ultimately be involved in neuroinflammation.